Dental Implants and Oral Rehabilitation in Immunocompromised Patients: A Systematic Review - Lana Ahmed Alaskar; Abdulrahman Abdulkader Jomah; Suliman Fahad Alfahaid; Mohammed Thafar Aldosari; Saud Khalid Alkhalid; Omar Ali Alghamdi (The Bioscan, 2024)
Objectives: To explore the success rates of dental implants in patients with compromised immune systems and the factors that influence their outcomes. Methods: A total of 412 pertinent publications were found after a comprehensive search across four databases. 68 full-text publications were examined after duplicates were eliminated using Rayyan QCRI and relevance was checked; six studies finally satisfied the requirements for inclusion. Results: We included six studies with a total of 930 patients, 1950 dental implants, and 486 (52.3%) were males. The follow-up period ranged from 12 to 87.6 months. The failure rates of dental implantation ranged from 5.6% in immunocmpromised patients to 19% in HIV patients. HIV-positive patients with controlled viral loads generally achieve implant success rates similar to healthy individuals, though they may face more soft-tissue issues and marginal bone loss. Diabetic patients exhibit higher failure rates, highlighting the importance of blood sugar control for better outcomes. For renal transplant patients on immunosuppressive therapy, implant success remains achievable with close monitoring. Conclusion: Dental implants are viable for immunocompromised patients with proper personalized care. HIV-positive and diabetic patients need focused management of soft-tissue and glycemic control, while renal transplant recipients benefit from close monitoring to detect complications early. Further research with larger studies and standardized methods is needed to improve guidelines and ensure safe, effective implant options for these high-risk patients.